1986
DOI: 10.1111/j.1432-1033.1986.tb10447.x
|View full text |Cite
|
Sign up to set email alerts
|

Metabolism of n-pentane by ethanol-inducible cytochrome P-450 in liver microsomes and reconstituted membranes

Abstract: The cytochrome P-450-dependent metabolism of n-pentane was studied by head-space gas chromatographic analysis of incubations with liver microsomes and reconstituted systems from rat and rabbit liver. The alkane was metabolized in liver microsomes from imidazole-treated rabbits at an apparent V,,, of 3 nmol mg-' min-and a K, of 35 pM and in liver microsomes from acetone-treated rats at an apparent V,,, of 10 nmol mg-' min-' and a K, of 9 pM. The rate of microsomal n-pentane metabolism was enhanced fivefold by a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
15
0

Year Published

1988
1988
2020
2020

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 42 publications
(15 citation statements)
references
References 30 publications
0
15
0
Order By: Relevance
“…When included in the incubations using microsomes from acetone-treated animals, PEITC acted as a competitive inhibitor with an apparent Ki of 1 PM. This value is lower than the apparent kinetic constants ( K , or Ki) of other previously reported substrates or inhibitors of this isozyme, having values ranging from 9 to 30 PM , Terelius and Ingelman-Sundberg 1986, and indicates a high affinity for binding at the active site. This probably contributed to the observed selective inhibition of microsomal NDMA demethylation compared to activities associated with other forms of P-450.…”
Section: Discussionmentioning
confidence: 62%
See 1 more Smart Citation
“…When included in the incubations using microsomes from acetone-treated animals, PEITC acted as a competitive inhibitor with an apparent Ki of 1 PM. This value is lower than the apparent kinetic constants ( K , or Ki) of other previously reported substrates or inhibitors of this isozyme, having values ranging from 9 to 30 PM , Terelius and Ingelman-Sundberg 1986, and indicates a high affinity for binding at the active site. This probably contributed to the observed selective inhibition of microsomal NDMA demethylation compared to activities associated with other forms of P-450.…”
Section: Discussionmentioning
confidence: 62%
“…NDMA, an environmentally prevalent procarcinogen, is a potent liver tumorigenic agent in rats (Magee et al 1976). It has previously been demonstrated that cytochrome P450 IIEl-an enzyme inducible by ethanol, acetone, pyrazole, isoniazid, fasting, diabetes, and other factors-is involved in the metabolism of a variety of small organic compounds including aniline, acetone, butanol, carbon tetrachloride, chloroform, ethanol, ether, benzene, and n-pentane (Morgan et al 1982, Johansson and Ingelman-Sundberg 1985, Koop and Casazza 1985, Johansson et al 1986, Terelius and Ingelman-Sundberg 1986. Microsomal P450 IIEl is also responsible for the initial a-hydroxylation of NDMA at low concentrations (ca.…”
Section: Introductionmentioning
confidence: 99%
“…Specifically, lipid hydroperoxides via a process known as β-scission, give arise to ethane or pentane, the former from fatty acids which have their first carbon-carbon double bond 3 carbon atoms from the terminal “omega” carbon (omega-3 or n-3 fatty acids) and the latter from omega-6 (n-6) fatty acids [ 1 ]. Since pentane can be metabolized in the liver to pentanol the interpretation of altered breath pentane concentrations is more complex that of ethane which does not undergo such metabolism [ 11 ]. Ethane is also highly volatile resulting in it being predominantly excreted in the breath where it can be assayed using thermal desorption gas chromatography mass spectrometry or light spectroscopy, it being found in concentrations ranging from approximately 0.5 to 5 PPB by volume in the exhalant of healthy individuals [ 6 , 12 ].…”
Section: Introductionmentioning
confidence: 99%
“…The effects of lipid peroxidation may be reduced and regulated by antioxidants (57). Saturated alkanes including ethane and pentane are considered the final products of lipid peroxidation and have been widely recognized as volatile biomarkers of this reaction in breath analysis (110). The production of C3-C11 saturated alkanes is also associated with lipid peroxidation, though the production of branched alkanes does not originate from this mechanism (111).…”
Section: Targeted Therapies Based On Non-invasive Detectionmentioning
confidence: 99%